New Advances on Pathophysiology of Diabetes Neuropathy and Pain Management: Potential Role of Melatonin and DPP-4 Inhibitors - Busa, Prabhakar; Kuthati, Yaswanth; Huang, Niancih; Wong, Chih-Shung (Frontiers in Pharmacology, 2022)
Pre-diabetes and diabetes are growing threats to the modern world. Diabetes mellitus (DM) is associated with comorbidities such as hypertension (83.40%), obesity (90.49%), and dyslipidemia (93.43%), creating a substantial burden on patients and society. Reductive and oxidative (Redox) stress level imbalance and inflammation play an important role in DM progression. Various therapeutics have been investigated to treat these neuronal complications. Melatonin and dipeptidyl peptidase IV inhibitors (DPP-4i) are known to possess powerful antioxidant and anti-inflammatory properties and have garnered significant attention in the recent years. In this present review article, we have reviewed the recently published reports on the therapeutic efficiency of melatonin and DPP-4i in the treatment of DM. We summarized the efficacy of melatonin and DPP-4i in DM and associated complications of diabetic neuropathy (DNP) and neuropathic pain. Furthermore, we discussed the mechanisms of action and their efficacy in the alleviation of oxidative stress in DM.